2012
DOI: 10.1902/jop.2011.100733
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cell Motility and Attachment With Titanium Surface Modifications

Abstract: Periodontal cells displayed differential motility and long-term attachment to titanium surfaces. Selective modification of titanium surface properties in various regions of an implant may be useful in guiding specific cell populations to specific locations where they might best aid in osseointegration and soft tissue remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Moreover, immortalized and/or xenogenic cell lines, which slightly reflect the expected behavior of healthy human cells of the peri-implant tissue, have been used. Other important aspects of cell behavior for a successful tissue integration of implant material, such as cell migration or quality of adhesion, are not the focus of early screening schemes [23,28]. To avoid time-consuming and expensive in vivo investigations of ultimately deficient materials, a more reliable in vitro examination is required in order to detect any biocompatibility issues during the initial in vitro screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, immortalized and/or xenogenic cell lines, which slightly reflect the expected behavior of healthy human cells of the peri-implant tissue, have been used. Other important aspects of cell behavior for a successful tissue integration of implant material, such as cell migration or quality of adhesion, are not the focus of early screening schemes [23,28]. To avoid time-consuming and expensive in vivo investigations of ultimately deficient materials, a more reliable in vitro examination is required in order to detect any biocompatibility issues during the initial in vitro screening.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that cells from mice have a seven times higher metabolic rate than those from humans and tumor cells differ in size, proliferation, and metabolism from healthy counterparts, which in part might be an explanation for the described discrepancies [68,69]. However, due to a better availability and an easier cultivation of primary fibroblasts compared to primary osteoblasts, several studies compared primary fibroblasts with immortalized osteoblasts when analyzing the cell-specific effects of an implant surface [23,70,71]. As the results of this study illustrate, this approach can lead to false conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that NaTi surface might provide a promising environment for PDL ligament-anchored implants in the future by regulating the proliferation rate, morphology and differentiation of PDL cells. Cell culture studies are valuable to investigate the biological interaction of new titanium surfaces/cells and provide to gain an initial insight regarding cell morphology, adhesion, migration, proliferation and differentiation on implant surfaces [7,53]. However, cell culture studies can not simulate the dynamic environment of bone/implant surface and in vivo performance of modified/novel implant surfaces should be confirmed in animal models and subsequent clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…PDL also plays an important role in the movement of teeth and in maintaining new homeostasis. [1][2][3] Technology that facilitates the regeneration of tooth must receive considerable attention, especially in prosthodontics. [4][5][6][7] In this case, the conventional regenerative dentistry has been developing stem cell technology, scaffolds and growth factors to produce biotechnological artificial teeth.…”
Section: Research Report Introductionmentioning
confidence: 99%